Berberine hydrochloride inhibits migration ability via increasing inducible NO synthase and peroxynitrite in HTR-8/SVneo cells. (6th April 2023) - Yang, Li-Jun; He, Jia-Bei; Jiang, Yu; Li, Jianzhong; Zhou, Zhen-Wei; Zhang, Chuan; Tao, Xia; Chen, Alex F.; Peng, Cheng; Xie, He-Hui
Abstract: Ethnopharmacological relevance: Inadequate trophoblasts migration and invasion is considered as an initial event resulting in preeclampsia, which is closely related to oxidative stress. Berberine hydrochloride (BBR), extracted from the traditional medicinal plant Coptis chinensis Franch., exerts a diversity of pharmacological effects, and the crude drug has been widely taken by most Chinese women to treat nausea and vomit during pregnancy. But there is no research regarding its effects on trophoblast cell function. Aim of the study: This study aimed to investigate the effect of BBR on human-trophoblast-derived cell line (HTR-8/SVneo) migration ability and its mechanism. Materials and methods: Cell viability was detected by CCK-8 assay. The effect of BBR on cells migration function was examined by scratch wound healing assay and transwell migration assay. Intracellular nitric oxide (NO), superoxide (O2 − ) and peroxynitrite (ONOO − ) levels were measured by flow cytometry. The expression levels of inducible NO synthase (iNOS), eNOS, p-eNOS, MnSOD, CuZnSOD, Rac1, NOX1, TLR4, nuclear factor-κB (NF-κB), p-NFκB, pro-inflammatory cytokines (TNF-α, IL-1β and IL-6) in cells were analyzed by Western blotting. Uric acid sodium salt (UA), the scavenger of ONOO −, PEG-SOD (a specific superoxide scavenger), L-NAME (a NOS inhibitor) and antioxidants (Vit E and DFO) were further used to characterize the pathway of BBR action. Results: 5 μM BBR decreased both the migration distance and the number of migrated cells without affecting cells viability in HTR-8/SVneo cells after 24 h treatment. BBR could increase the level of NO in HTR-8/SVneo cells, and the over-production of NO might be attributable to iNOS, but not eNOS. BBR could increase intracellular O2 − levels, and the over-production of O2 − is closely related with Rac1 in HTR-8/SVneo cells. The excessive production of NO and O2 − further react to form ONOO −, and the increased ONOO − level induced by BBR was blunted by UA. Moreover, UA improved the impaired migration function caused by BBR in HTR-8/SVneo cells. The depressed migration function stimulated by BBR in HTR-8/SVneo cells was diminished by PEG-SOD and L-NAME. Furthermore, BBR increased the expression of IL-6 in HTR-8/SVneo cells, and antioxidants (Vit E and DFO) could decrease the expression of IL-6 and iNOS induced by BBR. Conclusions: BBR inhibits the cell migration ability through increasing inducible NO synthase and peroxynitrite in HTR-8/SVneo cells, indicating that BBR and traditional Chinese medicines containing a high proportion of BBR should be used with caution in pregnant women. Graphical abstract: Image 1